PO.8.168 The third dose of mRNA COVID 19 vaccine is safe and efficacious for SLE patients receiving belimumab. (27th September 2022) - Tunitsky-Lifshitz, Y; Maoz-Segal, R; Iancovici-Kidon, M; Niznik, S; Shavit, R; Haj Yahia, S; Agmon-Levin, N
Abstract : Introduction: In the era of COVID-19 pandemic, data on safety and efficacy of anti-COVID vaccines in SLE patients is needed and scarce. Belimumab is a monoclonal antibody directed at BAFF, an essential cytokine in B cell survival, though it does not impair efficacy of some traditional vaccines. Thus, the aim of our study was to assess immunogenicity and safety of BNT162b2 Pfizer mRNA vaccine in SLE patients treated with Belimumab. Methods: SLE patients treated with Belimumab for at least 6 months in the Sheba Medical Center were included in this study. All were recommended to receive the BNT162b2 COVID-19 mRNA vaccine according to Ministry of Health recommendations, and thereafter to perform a serologic test for CoV-2 IgG 2–6 weeks after receiving the 2nd or 3rd doses. Clinical data included demographics, SLE treatments, adverse effects to the vaccine as well as SLEDAI scores performed 2 weeks before receiving 1st dose and 6 to 8 weeks after receiving 2nd and 3rd doses of the vaccine. Results: Our cohort included 17 patients, 15(88.2%) were females, median age was 50±14.2 years, and disease duration was 12±10.57 years. Median Belimumab treatment time was 6±2.5 years. In our cohort 2/17 received only 2 vaccine doses as thereafter the suffered mild COVID-19 infection, while 15/17 patients received 3-doses. Serologic assessment was performed for 10 patients, 7/10(70%) became seropositive following the second dose, while 2/3 patients seroconverted only after the 3rd dose. Vaccination was well tolerated with minimal adverse events and no disease flares (e, g. SLEDAI 7.7±5.19 and 7.82±5.2 before vaccination and post 3rd dose respectively). Conclusions: Immunization with 3 doses of BNT vaccine is safe and efficacious for SLE patients treated with Belimumab. Only following the 3rd dose immunogenicity of SLE patients in this cohort mounted to 90%, thereby approximating the general healthy population. Assessment of seroconversion and consideration of subsequent boosters' vaccine should be considered for SLE patients treated with Belimumab.